Kazakhstan’s Energy Diplomacy from Hydrocarbon Power to Decarbonization (International relations and international law Journal, 2026)
In the context of transforming global energy markets, accelerating decarbonization, and the digitalization of energy systems, energy diplomacy is acquiring new forms that go beyond the classical geopolitics of hydrocarbons. Kazakhstan-one of Eurasia’s major exporters of oil and gas-occupies a unique position at the intersection of a resource-based development model, great-power competition, and the imperatives of the energy transition. This article examines how changes in global energy markets and the diffusion of digital technologies are reshaping Kazakhstan’s energy diplomacy amid geoeconomic rivalry between the United States, China, and Russia.The study draws on concepts from geoeconomics, energy security, and the international political economy of the energy transition, extending them through the incorporation of digitalization and climate governance. Methodologically, the paper employs a three-case analytical design comprising the Trans-Caspian transport corridor as an infrastructure-geopolitical case, Kazakhstan’s Emissions Trading System (KAZ ETS) as an institutional-climate case, and the digitalization of the electricity grid led by KEGOC as a technological-governance case.The findings demonstrate that Kazakhstan’s energy diplomacy is evolving into a hybrid form in which hydrocarbon power, transit infrastructure, and digital-climate instruments function as mutually reinforcing sources of geoeconomic influence. Diversification through the Trans-Caspian corridor reduces transit dependence on Russia, KAZ ETS enhances institutional compatibility with European climate regimes, and energy digitalization improves sectoral governance and investment attractiveness. Together, these dynamics expand Kazakhstan’s foreign-policy autonomy and access to markets and green finance.More broadly, the article shows that in the era of energy transition, power in energy is increasingly shaped not only by control over resources but also by control over infrastructure, data, and regulatory standards. Kazakhstan’s experience illustrates how middle powers can leverage the energy and digital transition to strengthen their geoeconomic position in a multipolar system.Key words: Energy diplomacy; Kazakhstan; energy transition; decarbonization; energy digitalization; Trans-Caspian corridor; KAZ ETS; geoeconomics